Proyecto de inversión para la creación de una empresa Pisícola Productora de Tilapia para la venta a nivel Nacional e Internacional ubicada en el Cantón Paltas, Provincia de Loja - Loaiza Tinoco, Jorge Leonardo (2016)
The realization of this "INVESTMENT PROJECT FOR THE CREATION OF A PRODUCER OF TILAPIA fish COMPANY FOR SALE AT NATIONAL AND INTERNATIONAL LEVEL LOCATED IN THE Paltas Canton, Loja province." Its main purpose the presentation of this practical and useful work as a fundamental support for economic development and business growth in society. So it was necessary to carry out the specific objectives mentioned in conducting market research, technical studies, legal - administrative and financial evaluation yielded information on the viability of the project. Besides scientific, deductive, analytical, mathematical, inductive, and essential for the structural development of statistical methodology thesis was handled. Attesting to compliance with the first objective was necessary to conduct a market study where demand and supply necessary to meet the opportunity and necessity of dispensing the product nationally and internationally analyzed. From this, several important points were determined on exports, establishing that these have been declining steadily since some years ago while imports of tilapia in the country almost non-existent, however, global consumption of tilapia is growing so that 5 total demand from a single company that is willing to absorb all the production company and continue the productive chain to the final consumer was determined. The second objective technical study indicating their location and installed capacity used, machinery and equipment, talent plus all essential and necessary production processes for operational and administrative functioning was established. The third goal allowed developing the legal organization as stipulated in the constitution of our country in the Fisheries Act and Fisheries Development. It also provided an internal organizational structure, establishing organizational and operating manuals for productive work of the company in all its periods. The fourth objective is embodied as conducting a financial study determining the project's initial investment and profitability to be obtained on a projection of five years, and finally financial indicators as VAN applied; TIR; RBC and sensitivity analysis, being friendly and sustainable.